2021
DOI: 10.3390/nu13010213
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of the “Omega Kid” Study Protocol: A Double-Blind, Randomised, Placebo-Controlled Trial Investigating the Effect of Omega-3 Supplementation on Self-Regulation in Preschool-Aged Children

Abstract: Self-regulation, the regulation of behaviour in early childhood, impacts children’s success at school and is a predictor of health, wealth, and criminal outcomes in adulthood. Self-regulation may be optimised by dietary supplementation of omega-3 long-chain polyunsaturated fatty acids (n-3 LCPUFAs). The aim of the “Omega Kid” study is to investigate the feasibility of a protocol to investigate whether n-3 LCPUFA supplementation enhances self-regulation in preschool-aged children. The protocol assessed involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…The strengths of this study include: (1) a protocol that was found to be feasible and acceptable by participating families [28]; (2) the use of a highly bioavailable novel omega-3 supplement; (3) successful blinding of the treatment with no difference between groups for parents correctly guessing their child's treatment allocation; (4) the use of validated outcome measures such as the PUFA FFQ; (5) and a specific focus on self-regulation, with previous studies in this age group focussing more broadly on cognitive functions [22][23][24]. Another strength is measuring HS-Omega-3 Index ® as recommended by the International Study for the Fatty Acids and Lipids (ISSFAL) Official Statement Number 6: the importance of measuring blood omega-3 long chain polyunsaturated fatty acid levels in research [56].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The strengths of this study include: (1) a protocol that was found to be feasible and acceptable by participating families [28]; (2) the use of a highly bioavailable novel omega-3 supplement; (3) successful blinding of the treatment with no difference between groups for parents correctly guessing their child's treatment allocation; (4) the use of validated outcome measures such as the PUFA FFQ; (5) and a specific focus on self-regulation, with previous studies in this age group focussing more broadly on cognitive functions [22][23][24]. Another strength is measuring HS-Omega-3 Index ® as recommended by the International Study for the Fatty Acids and Lipids (ISSFAL) Official Statement Number 6: the importance of measuring blood omega-3 long chain polyunsaturated fatty acid levels in research [56].…”
Section: Discussionmentioning
confidence: 99%
“…This manuscript adheres to the CONSORT guidelines for pilot and feasibility trials (Table S1 CONSORT Checklist). The feasibility of the study protocol has been assessed and reported elsewhere [28].…”
Section: Study Design and Participant Criteriamentioning
confidence: 99%
See 2 more Smart Citations